Role of the alfa1- and alfa2-adrenoceptors of the lateral hypothalamus in the dipsogenic response to central angiotensin II in rats - Ferrari, Antonio Carlos [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP]; Saad, Wilson Abrão [UNESP]; Renzi, Antonio [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1991)
The present experiments were conducted to investigate the role of the α1- and α2-adrenergic receptors of the lateral hypothalamus (LH) on the drinking response elicited by intracerebroventricular (i.c.v) injections of carbachol and angiotensin II (AII) in rats. Clonidine (an α2-adrenergic agonist) injected into the LH produced a dose-dependent reduction of the drinking responses elicited by i.c.v. administration of carbachol and AII. The α1-adrenergic agonist phenylephrine injected into the LH reduced the dipsogenic response to i.c.v. AII, but not to carbachol. Injection of yohimbine (an α2-adrenergic antagonist) and prazosin (an α1-adrenergic antagonist) into the LH also reduced the water intake produced by i.c.v. injection of AII. Previous injection of α1- or α2-adrenergic antagonists into the LH increased the antidipsogenic effect of clonidine or phenylephrine injected into the same area on the water intake induced by i.c.v. AII. These results show that the α1- and α2-adrenergic receptors of the LH are involved in the control of drinking responses elicited by i.c.v. injection of AII in rats. They also show that clonidine, but not phenylephrine, suppresses the drinking induced by i.c.v. carbachol. The data suggest that the discharge of central α-adrenergic receptors has a dual (inhibitory and excitatory) effect on water intake induced by central AII. © 1991.
Keywords: Adrenergic receptor; Angiotensin II; Lateral hypothalamus; Water intake; Alpha adrenergic receptor; Angiotensin; Carbachol; Clonidine; Phentolamine; Phenylephrine; Prazosin; Yohimbine; Animal experiment; Animal tissue; Controlled study; Drinking; Intracerebroventricular drug administration; Lateral hypothalamus; Male; Nonhuman; Priority journal; Rat; Adrenergic alpha-Agonists; Adrenergic alpha-Antagonists; Animal; Brain; Carbachol; Drinking; Hypothalamic Area, Lateral; Injections, Intraventricular; Male; Rats; Rats, Inbred Strains; Receptors, Adrenergic, alpha; Support, Non-U.S. Gov't; Water Deprivation